Suprema Lex Esto Principle and its Implementation - Nugroho, Hibnu (Frontiers in Law, 2024)
The Suprema Lex Esto principle is debated when applied as a rationale in the implementation of Government Regulation instead of Law Number 1 of 2020 concerning State Financial Policy and Financial System Stability for Handling the COVID-19 Pandemic, the discretion of handling COVID-19 and its impact using the basis of this principle raises a prohibition to make cases or crimes if problems arise. All state expenditures in the field of handling Covid 19 which function to protect the public cannot be said to be state losses. From this background, the problem arises How is the Implementation of the Suprema Lex Esto Principle during the COVID-19 emergency in Indonesia? This research has an object of law research, so this research is juridical research. Because the focus of the study is on the Application of the Suprema Lex Esto Principle during the Covid 19 Emergency, this includes juridical methods in a broad sense, so the approach method used is the empirical method.